Dinamika Harga Saham: Dampak dari Asset Growth, Net Profit Margin, ROI dan Islamic Social Reporting - Rachmania Sabilla, Meyra; Arwani, Agus (Shafin: Sharia Finance and Accounting Journal, 2023)
The stock price is the price of a stock in the form of evidence of capital participation in a company and has data that tends to fluctuate or always change. This study aims to determine how the effect of asset growth, net profit margin, return on investment and Islamic social reporting on stock prices. This research is included in the type of causal associative research with a quantitative approach. The population in this study is all property and real estate sector companies listed in the Sharia Securities List for the period 2018 – 2022 which amounted to 98 companies. The sampling technique in this study used purposive sampling techniques, with a total sample of 14 companies. The data analysis used in this study is descriptive statistical analysis, classical assumption test, multiple linear regression test, t-test, F test, and coefficient of determination. Based on the results of the t-test (partial), shows that the asset growth variable has no effect on stock prices, the net profit margin variable has a negative and significant effect on stock prices, while the return on investment and Islamic social reporting variables have a positive and significant effect on stock prices. The results of the F test (simultaneous) show that the variables asset growth, net profit margin, return on investment, and Islamic social reporting simultaneously affect stock prices.